Investigation of Two Different Pressure-Based Controlled Ice Nucleation Techniques in Freeze-Drying: The Integral Role of Shelf Temperature After Nucleation in Process Performance and Product Quality - Wenzel, Tim; Gieseler, Margit; Gieseler, Henning (Journal of Pharmaceutical Sciences, 2020)
The purpose of this study was to investigate the impact of shelf temperature modifications during application of controlled ice nucleation techniques on process data and critical product quality attributes for a challenging, high-concentration and high-fill volume amorphous model system. Different freezing programs were applied and compared for the mechanistically different depressurization and vacuum-induced surface freezing techniques. Critical process data, such as product temperature and drying time, were analyzed. The final products were characterized with a focus on product morphology, residual moisture, reconstitution time and stability. The shelf temperature directly after primary nucleation showed a major influence on process performance and product quality attributes, with an isothermal hold step at an intermediate temperature leading to optimal results in terms of homogeneity and reduction of product temperatures and drying time for the model system used. The different controlled ice nucleation techniques led to significantly different results in terms of product morphology and process data, showing that the two mechanistically different controlled nucleation techniques are not interchangeable.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Amorphous; Controlled ice nucleation; Depressurization technique; Freeze-drying; Lyophilization; Reconstitution time; Residual moisture; Scanning electron microscopy; Vacuum-induced surface freezing